PENGARUH IMPLEMENTASI KEBIJAKAN ENHANCED RELATIONSHIP BANKING TERHADAP KUALITAS PELAYANAN PADA PT. BCA, Tbk. CABANG PALU - Sasmita, Dinar Fisa (Katalogis, 2013)
This study aims to determine the level of influence the implementation of policies enhanced relationship to the quality of service at PT. Bank BCA, Tbk. Palu Branch. Program of Bank BCA banking relationship is a close relationship with the customer enables us to get to know customers and their needs better than competitors, so we can help customers with solutions and superior service - where competition is difficult and / or take a long time to build competency. Policy implementation Nugroho opinion, nothing related to the way in order to achieve policy goals. Implemented through the form of programs and through derivatives. Derivatives are defined is through project interventions and intervention activities. Activities in the management of policy implementation can be arranged sequentially among others, 1) Implementation Strategy (praimplementasi), 2) Organizing (Organizing), 3) mobilization and leadership; 4) Control. In this study, using quantitative methods of data analysis techniques used in data processing are Simple Linear Regression Analysis. The sample in this study consisted of Employee and Customer Bank BCA. Sampling techniques that researchers use to study is accidental sampling. The results showed that the independent variables in this study are Enhanced Relationship Policy Implementation have influence with the dependent variable Service Quality Bank BCA. Based on the results of a simple regression analysis treated the Enhanced Relationship Policy Implementation have an influence on service quality BCA with value - average interval coefficients between 0.60 to 0.799 and included in the category of a strong relationship level.